Kepemimpinan Kepala Sekolah dalam Pengelolaan Program Hafalan Qur’An di SMP Sains Qur’an Al Iman - Hariski Hariski; Apri Eka Budiyono; Giman Bagus Pangeran (Jurnal Manajemen Bisnis Digital Terkini, 2026)
The management of the Qur'an memorization program at Al Iman Quran Science Junior High School by school administrators is covered in this paper. One of the school's main initiatives is the Qur'an memorization program, which aims to develop students' character via memorization and study of the Qur'an while also raising educational standards. This study employs a descriptive method in conjunction with a qualitative approach. The principal and Tahfidz instructors who are actively involved in the program's execution make up the research subjects. Interviews, observations, and documentation were used to gather data. According to research findings, school leadership plays a significant role in teacher development by offering training to enhance teacher competency and working to promote collaboration with parents of children. Four Qur'anic teacher support each class while the memorization method is implemented in an organized and disciplined manner. For students in the first and second grades, audio and the Hijaz Wafa-style Qur'anic reading method are employed as educational resources. Regular memorizing competitions organized by the school and the education administration each year are supporting aspects for this program. Meanwhile, differences in kids' remembering skills and parents' lack of interest in and support for their children's at-home learning activities are examples of limiting factors.